The rheological characterisation of non- Newtonian slurries using a novel balanced beam tube viscometer - Slatter, Paul Thomas (Department of Civil Engineering, 2016)
The novel Balanced Beam Tube Viscometer (BBTV), developed at the University of Cape Town, has been further developed and refined. Extensive work has been done in the following areas: (i) The effective length of the BBTV tubes. (ii) Interpretation of the data obtained using the BBTV in both the laminar and turbulent flow regimes. (iii) Comparison with the rotary type viscometer. Kaolin clay and uranium tailings slimes slurries of different particle size range and concentration have been successfully characterised by yield- pseudoplastic rheologies using the BBTV. The BBTV is in fact a miniature pipeline and it has been shown that it is capable of producing valid turbulent flow data and indicating the laminar/turbulent transition region in the two tube sizes .